The Roles of Neurotensin and its Analogues in Pain - Feng, Yu-Peng; Wang, Jian; Dong, Yu-Lin; Wang, Ya-Yun; Li, Yun-Qing (Current Pharmaceutical Design, 2015)
Neurotensin (NT) is an endogenous 13 amino acid neuropeptide with profound opioid-independent analgesic effects. This role of NT is thought to be mediated by both neurotensin receptor subtype 1 (NTS1) and neurotensin receptor subtype 2 (NTS2). NT and its receptors are widely distributed in the pain circuits in central nervous system. Thus NT might modulate pain in many structures of pain pathway, such as spinal cord, rostroventral medulla (RVM) and periaqueductal gray (PAG). Actually either intrathecal application of NT or direct injection of NT into RVM or PAG or intracerebroventricular injection of NT showed analgesic effects. NT exerted its antinociceptive effects in both acute pain and chronic pain models. The analgesic effects of NT were originally found in acute pain experiments. In the case of pathological pain, for example, formalin injection induced inflammatory pain and sciatic nerve constriction induced neuropathic pain, NT also shows antinociceptive effects. The effects exist in somatic pain as well as visceral pain induced by noxious colorectal distension (CRD) or writhing test. It should be noted that NT plays an important role in stress-induced antinociception (SIAN), especially in higher intensity stress experiments. However as a neuropeptide, NT is susceptible to degradation by peptidases and cannot cross the blood-brain barrier (BBB). Great efforts have been made to find NT analogues that are more biologically stable and could inhibit pain by systematic administration. The present review focuses on the analgesic role and the underlying mechanisms of NT and its analogues in pain, especially in chronic pain models.
Keywords: analgesia